2019
DOI: 10.1101/2019.12.20.884866
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic and morphological variation is associated with differences in cold-water tolerance and geographic expansion among invasive snails (Melanoides tuberculata) in central Texas

Abstract: 24Melanoides tuberculata (Thiaridae) is an old-world freshwater snail that is and now 25 circumtropical. After being introduced in the 1960s via the aquarium trade, populations of M. 26 tuberculata are thriving in spring systems of Texas (USA). Field surveys and experimental 27 investigations of temperature tolerance suggest M. tuberculata is stenothermal, and thus range 28 expansions outside of aquatic habitats with water temperatures between 18° and 32°C should be 29 unlikely. However, in 2012 snails were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
(76 reference statements)
1
4
0
Order By: Relevance
“…Also, these families have a high adhesion ability to the rocky substrates. This finding in line with previous studies indicating that the rivers with strong current and a rocky bottom substrate become the habitat for most of the gastropods from Thiaridae and Neritidae families (Dharma 1988;Subba Rao 1989;Appleton 2003Appleton , 2015Abdou et al 2015;Harding et al 2019;Purnama et al 2019;Sirza et al 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Also, these families have a high adhesion ability to the rocky substrates. This finding in line with previous studies indicating that the rivers with strong current and a rocky bottom substrate become the habitat for most of the gastropods from Thiaridae and Neritidae families (Dharma 1988;Subba Rao 1989;Appleton 2003Appleton , 2015Abdou et al 2015;Harding et al 2019;Purnama et al 2019;Sirza et al 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Despite this taxonomic uncertainty, the current study demonstrates the value of a phylogenetic analysis of molecular data to resolve the history of invasive species (however see [52]). The inclusion of 49 sequenced individuals from this study along with a geographically diverse sample of GenBank sequences, and the outgroup Paludomus siamensis, Paludomidae, the presumed sister lineage [7,16,24,30,48]. In contrast, shell morphology was not found to be a useful tool to evaluate invasion dynamics (Fig 3).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found that invaded regions have a high degree of haplotype overlap with native regions and provide estimates of invasion events. For instance, Facon et al [24] showed at least six invasion events in South and Central America, while Harding et al [30] suggested multiple invasions have occurred in central Texas. These studies and our current results demonstrate that multiple invasions are common for freshwater snails and provide evidence that propagule pressure is a driving factor for these successful invasions [54,55].…”
Section: Genetic Diversity and Invasion Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…);Gregoric et al (2011);Harding et al (2019);Purnama et al (2019);Barbosa et al (2020);Barros et al (2020);Khanam et al (2020);Lopes et al (2020); Okumura and Rocha (2020); Oliveira et al (2020) Song et al (2020); Alfaro et al (2021); Cano-Pérez et al (2021); Dumidae et al (2021); Harahap et al (2021); Lopes et al (2021); McClure (2021).…”
mentioning
confidence: 99%